2012
DOI: 10.1016/j.jadohealth.2011.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Attitudes of Latino Parents Toward Confidential Health Services for Teens

Abstract: Objectives To explore the knowledge and attitudes that Latino parents have about confidential health services for their teens and identify factors that may influence those attitudes. Methods Latino parents of teens (12-17 years old) were randomly selected from a large health maintenance organization and a community-based hospital to participate in one-hour focus groups. We conducted eight focus groups in the parent's preferred language. Spanish and English transcripts were translated and coded with inter-cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 20 publications
2
11
1
Order By: Relevance
“…Perhaps this subset of parents hold the misconception that EC causes abortions, which is condemned by many religious belief systems. Consistent with prior research 10 , this study also found that parental trust in the clinician improved parental acceptability.…”
Section: Discussionsupporting
confidence: 89%
“…Perhaps this subset of parents hold the misconception that EC causes abortions, which is condemned by many religious belief systems. Consistent with prior research 10 , this study also found that parental trust in the clinician improved parental acceptability.…”
Section: Discussionsupporting
confidence: 89%
“…Relying on the families’ goodwill to provide a personal doctor–patient space in the case of underage adolescents can make it difficult not only to create an adequate atmosphere of trust but also to talk about confidentiality, which makes it hard for the physician to have the possibility of explaining, in detail, what such confidentiality is and how it is going to be involved in what is spoken about during the consultation. Likewise, even if this doctor–patient space is achieved with the adolescent, scientific evidence shows that many parents want to be subsequently informed of what was talked about during the consultation, seeing this fact as a parental right [ 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that parents often have conflicting feelings about their child receiving confidential care. 21,22 However, the majority of parents support the idea that their adolescent child has the opportunity to spend time alone with the physician. 23 Parents with a high level of trust in their child's physician have been found to be more comfortable with their children having confidential consultations.…”
Section: Discussionmentioning
confidence: 99%